A Framework to Achieve Quality and Excellence in Higher Education: A Literature Review - Dr. S.M. Tariq Zafar; Prof. (Dr.) D.S. Chaubey; Yahya Al-Sarhani (International Journal of Engineering and Management Research, 2019)
Educating large numbers of people to a high standard and disseminating knowledge can be considered as the main objectives of today’s higher education sector. An effective framework for delivery mechanism by enhancing the functional responsibility and its effective execution will help the nation in achieving quality and excellence in higher education. Present paper tries to explore framework for achieving quality and excellence in higher education by analysing the various functional aspect of higher educational system in the country. After extensive literature survey and analysing the research work of eminent researchers and thinkers, it is concluded that higher education has become larger and more central to society and individuals; hence, there a need to develop framework including different functional components for performance indicator and measurement. It is suggested that various enhancement function should be executed primarily in systems of high trust, whereas the accountability function has to be developed to prevent bad quality of institutions and programs, and thus to protect the beneficiaries i.e. students and society. Universities need to be consciously and explicitly managing the processes associated with the creation of their knowledge assets and to recognise the value of their intellectual capital to their continuing role in society and in a wider global marketplace for higher education.